The U-shaped relationship between vertical integration and competition: Theory and evidence - Philippe Aghion; Rachel Griffith; Peter Howitt (Institute for Fiscal Studies (IFS), 2006)
This paper considers how competition can affect aggregate innovative activity through its effects on firms' decision whether or not to vertically integrate. A moderate increase in competition enhances innovation incentives, too much competition discourages innovative effort. These effects generates an inverted-U relationship between competition and innovation and between competition and the incentive to vertically integrate. Preliminary evidence finds that there is a non-linear relationship between competition and the propensity of firms to vertically integrate. These results seem to be more consistent with the Property Right Theory (PRT) of vertical integration than with the Transaction Cost Economics (TCE) approach.
Keywords: 330